PENGARUH PENGENDALIAN INTERNAL DAN KOMPETENSI AUDITOR TERHADAP EFEKTIVITAS PELAKSANAAN PROSEDUR AUDIT DALAM PENCEGAHAN FRAUD (Studi Pada Auditor Inspektorat Kota Kendari) - Kadir, Hernawari (JURNAL AKUNTANSI, 2017)
ABSTRACT Maneuver of  fraud be complicated both in governance and in the company that it’s development is very difficult to detect for, as one of the government's efforts in this regard to reduce cases of fraud is one of them through effective monitoring system, to enhance the role and the functions of the Government Internal Control Apparatus (APIP) in particular Government Inspectorate of Kendari.This study uses primary data through questionnaires distributed to the Auditor and the Inspectorate PPUPD Kendari. The sample was determined by cencus (complete enumeration) for the target population or the respondent relative  is not too large. Questionnaires were distributed as much as 28 questionnaires, and questionnaires were collected as many as 28 questionnaires. Data analysis method used multiple linear regression analysis using IBM SPSS 20.The results of this research  that, (1) Internal control significantly influence the effectiveness of the audit procedures in prevention of fraud, (2) the auditor competence but no significant effect on the effectiveness of audit procedures in prevention of fraud, (3) Internal control and competence of auditors influential significantly to the effectiveness of the implementation to audit procedures in prevention of fraud.Keywords : internal control, auditor competence, fraud prevention, multiple                       linier regression analysis.